(untitled) (Computer Aided Drug Development, 2024)
Author Dr. Madhavi Latha Samala Associate Professor, Department of Pharmaceutics, Aditya College of Pharmacy, Aditya University, Surampalem, Andhra Pradesh, India Abstract The integration of computing technologies in pharmaceutical research and development has raised significant legal, ethical, and market-related considerations. Legal frameworks protect innovative computational methods in pharmaceutical R&D, addressing intellectual property rights, patents, and proprietary software protection. Ethical considerations encompass data privacy, algorithm transparency, and responsible use of artificial intelligence in drug discovery. Market analysis through computational tools has transformed decision-making processes, enabling precise prediction of drug market potential, competitive analysis, and strategic planning. These interconnected aspects form a crucial foundation for modern pharmaceutical development, where computing technologies must balance innovation protection with ethical responsibilities while delivering valuable market insights. Keywords: Intellectual Property Rights; Pharmaceutical Computing; Research Ethics; Market Analysis Tools; Data Protection; Patent Law; Digital Innovation View PDF